Important features in text presentation for children with dyslexia - Ismail R.; Jaafar A. (Asian Research Publishing Network (ARPN), 2023)
Information and communication technology (ICT) plays an important role in providing solutions, support and hope for children with dyslexia. Teachers and parents acknowledge the capability of ICT to assist children in acquiring the lessons taught using educational courseware. Teaching dyslexic students requires more than just basic multimedia applications. Customized applications with an emphasis on special techniques are important to engage students with normal educational subjects. Research and studies in this area actively utilize the human-computer interaction (HCI) to increase the usability and success rate when developing a dyslexic's educational courseware. We conducted a few experiments to investigate the usage of text as one of a number of interesting features by which to increase usability. The interaction behaviors of children with dyslexia in the focus groups were then observed and analyzed. This paper reports the research findings that elaborate on how different formats of text can influence successful interaction in designing educational courseware for children with dyslexia. © 2005 - 2014 JATIT & LLS. All rights reserved.